Short Communication: Species diversity of macroalgae in Teluk Bidara Beach, Dungun, Terengganu, Peninsular Malaysia - NURIN KARMILA KAUJ; SITI NUR LIYANA ROSLAN; NUR FARAH AIN ZAINEE; NOR BAZILAH RAZALI; NOR AZLIZA ISMAIL; NUR AMALINA MOHD IZAM; FARAH AYUNI FARINORDIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kauj NK, Roslan SNL, Zainee NFA, Razali NB, Ismail NA, Izam NAM, Farinordin FA. 2024. Short Communication: Species diversity of macroalgae in Teluk Bidara Beach, Dungun, Terengganu, Peninsular Malaysia. Biodiversitas 25: 4370-4378. Macroalgae are a diverse group of organisms with varying physical characteristics, genetic relationships, morphologies, sizes, colors, and chemical compositions. Research on macroalgae in Malaysia has shown significant expansion. Nevertheless, the current inventory of macroalgae in the East Coast of Peninsular Malaysia is limited. This study was conducted to analyze the species diversity and morphologies of macroalgae in Teluk Bidara, Terengganu, Malaysia. Specimens were collected at low tides. Wet specimens were preserved in 10% formalin while herbarium preparation was conducted to preserve dried specimens. Specimens were observed under microscopes to determine the distinguishable morphological characteristics. There were 17 species of macroalgae recorded with Ochrophyta was the phylum with the greatest number of species (47%), followed by Rhodophyta (35%), and Chlorophyta (18%). The calculated Shannon-Wiener’s Index (2.833) and Simpson's Index (0.9412) indicate a significant amount of species diversity, suggesting that the community includes many species with an even distribution of individuals. The diverse range of Sargassum is attributed to their habitat diversity, adaptability, reproductive strategies, genetic diversity, distribution patterns, ecological interactions, and anthropogenic activities. Malaysia's coastal and island ecosystems are known to house a significant number of macroalgae species, providing suitable habitats for maintaining their diversity. Macroalgae diversity and its habitats, being part of the natural heritage, should be adequately preserved.